(untitled) (Global Journals of Research in Engineering, 2025)
High-energy ions have the potential to damage the walls of nuclear fusion Tokamak reactors As a result it is essential to establish dependable methods for determining whether the materials are still resilient This investigation examines the most effective methods for assessing the reliability of materials that contain tritium plasma in graphene crystals The impact of varying energy levels from 5 keV to 35 keV on tritium plasma was investigated using molecular dynamics in a computer simulation to investigate the retention mechanisms The quantity of tritium retained Shannon entropy based on kinetic energy and Shannon entropy are all factors that are used to calculate reliability A valuable instrument for comparing various categories of tritium plasma on graphene crystals with kinetic energies ranging from 5 keV to 35 keV are the Pearson correlation coefficients The designer can employ Pearson Correlation to ascertain the most efficient structural reliability computation method for a variety of reliability calculations This research simplifies the process of selecting plasma-resistant materials for nuclear fusion applications and allows designers to enhance the design of reactor walls